Mandatory retrieval test to incentivize retrieval practice of physics principles - Vegard Gjerde; Martino Marisaldi; Kjellmar Oksavik; Kjartan Olafsson; Harald Spångberg; Bodil Holst (Physical Review Physics Education Research)
Students and educators often face time constraints, making it essential to develop interventions that are both easy to implement and have a substantial impact on learning and performance. One promising strategy is retrieval practice, particularly in the context of physics education, where many students struggle with basic knowledge. Prior research has shown that retrieval practice improves self-explanation and problem-solving performance, yet many students avoid it, even when resources are provided. To address this, we introduced a mandatory retrieval test with a minimum benchmark of 50% to encourage greater engagement with retrieval practice. The primary aim of this study was to explore students’ experiences with the test and its impact on their use of retrieval practice. A secondary aim was to examine whether increased retrieval practice effort correlated with improved performance on factual, conceptual, and problem-solving exams. Interviews with 13 students revealed that about half crammed for the test, while the other half spaced their practice throughout the semester. Several students noted that the test motivated them to both memorize and understand the principles, with no complaints about the mandatory test. Of the 463 students, 179 achieved a perfect score, suggesting substantial engagement. Effect sizes on factual, conceptual, and problem-solving performance tests ranged from negligible to large, indicating substantial potential benefits with minimal risk. In conclusion, the mandatory retrieval test is an effective, low-effort intervention for educators, promoting greater student adoption of retrieval practice and yielding both qualitative and quantitative evidence of enhanced learning and performance.